SIU-ICUD: Comprehensive Imaging in Prostate Cancer—A Focus on MRI and Micro-Ultrasound - Cesare Saitta; Wayne G. Brisbane; Hannes Cash; Sangeet Ghai; Francesco Giganti; Adam Kinnaird; Daniel Margolis; Giovanni Lughezzani (Société Internationale d’Urologie Journal, 2025)
Background/Objectives: The diagnostic approach to prostate cancer (PCa) has evolved from systematic biopsies to imaging-guided strategies that improve detection of clinically significant PCa (csPCa) while reducing overdiagnosis. Multiparametric magnetic resonance imaging (mpMRI) has emerged as the gold standard for pre-biopsy evaluation, while micro-ultrasound (MicroUS) offers a promising alternative with real-time imaging capabilities. Methods: We examined the principles, image interpretation frameworks (Prostate Imaging Reporting and Data System (PI-RADS) and Prostate Risk Identification using Micro UltraSound (PRI-MUS)), and clinical applications of mpMRI and MicroUS, comparing their diagnostic accuracy in biopsy-naïve patients, repeat biopsy scenarios, active surveillance, and staging. Results: mpMRI improves csPCa detection, reduces unnecessary biopsies, and enhances risk stratification. Landmark studies such as PRECISION (Prostate Evaluation for Clinically Important Disease: Sampling Using Image Guidance or Not?) and PRIME (Prostate Imaging Using MRI±Contrast Enhancement) confirm its superiority over systematic biopsy. However, mpMRI remains resource-intensive, with limitations in accessibility and interpretation variability. Conversely, MicroUS, with its high-resolution real-time imaging, shows non-inferiority to mpMRI and potential advantages in magnetic resonance imaging (MRI)-ineligible patients. It improves lesion visualization and biopsy targeting, with ongoing trials such as OPTIMUM (Optimization of prostate biopsy—Micro-Ultrasound versus MRI) evaluating its standalone efficacy. Conclusions: mpMRI and MicroUS are complementary modalities in PCa diagnosis. While mpMRI remains the preferred imaging standard, MicroUS offers an alternative, particularly in patients with MRI contraindications. Combining these techniques could enhance diagnostic accuracy, reduce unnecessary interventions, and refine active surveillance strategies. Future research should focus on integrating both modalities into standardized diagnostic pathways for a more individualized approach.